The role of mineral fertilizers in transforming agriculture in Indonesia - Yasmin, Fitria (International Food Policy Research Institute, 2014)
Indonesia is an archipelago consisting of 13,466 islands, which are divided into 33 provinces. Java, Bali, and Nusa Tenggara are the inner islands and contain 62 percent of the total population of 246 million, but only accounts for 8 percent of the total land area. The inner islands are naturally more fertile than the outer islands that have nutrient-poor, acidic soils. In theory, fertilizer use should be higher on the outer islands, but in reality outer island fertilizer use is generally lower, making crop yields lower, especially when compared to Java. There are approximately 15 million farmer households in Indonesia cultivating rice and 6.7 million cultivating maize. Approxi-mately 68 percent of rice farmers and 37 percent of maize farmers use chemical fertilizers, according to the 2009 Agriculture Census.